Identifying peer‐to‐peer communities in the network by connection graph analysis. (29th May 2014) - Jusko, Jan; Rehak, Martin
SUMMARY In this paper we present a unified solution to identify peer‐to‐peer (P2P) communities operating in the network. We propose an algorithm that is able to progressively discover nodes cooperating in a P2P network and to identify that P2P network. Starting from a single known node, we can easily identify other nodes in the P2P network, through the analysis of widely available and standardized IPFIX (NetFlow) data. Instead of relying on the analysis of content characteristics or packet properties, we monitor connections of known nodes in the network and then progressively discover other nodes through the analysis of their mutual contacts. We show that our method is able to discover cooperating nodes in many P2P networks and present the real computational requirements of the algorithm on a large network. The use of standardized input data allows for easy deployment onto real networks. Copyright © 2014 John Wiley & Sons, Ltd.